Vortex creep activation energies and depinning currents in CaKFe4As4 and Ba0.6K0.4Fe2As2 revealed by AC susceptibility measurements. (22nd July 2020) - Wang, Chunlei; He, Tian; Han, Qianqian; Ji, Zhichao; Lei, Qiankun; Tang, Qingbin; Li, Yingbin; Yu, Benhai
Abstract: Systematic ac susceptibility measurements have been carried out to study the vortex dynamics in CaKFe4 As4 and Ba0.6 K0.4 Fe2 As2 single crystals under various temperatures, dc magnetic fields, ac field frequencies and amplitudes. The field-temperature phase diagrams were shown, and the characteristics of irreversibility line were also derived. The specific expressions of activation energy on the parameters of temperature ( T ), current density ( J ), and dc magnetic field ( H ) are obtained according to these data. The results indicate that both superconductors have similar functional expressions of activation energy and flux pinning behaviors. Though both CaKFe4 As4 and Ba0.6 K0.4 Fe2 As2 superconductors exhibit very strong flux pinning ability, the vortex pinning potential in CaKFe4 As4 is slightly smaller than that in Ba0.6 K0.4 Fe2 As2, which may result from its distorted FeAs4 -tetrahedron in CaKFe4 As4 . The depinning critical current densities at the limit of low temperature and low field were also extrapolated, yielding the corresponding values of J c0 (0) ∼ 1.0 × 10 8 and 2.2 × 10 8 A cm −2 for CaKFe4 As4 and Ba0.6 K0.4 Fe2 As2 superconductors, respectively, which suggest potential applications.